2018
DOI: 10.1111/asj.13003
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide association studies for two exterior traits in Chinese Dongxiang spotted pigs

Abstract: Pigs show extensive variation in exterior appearance. This variation has been explored as one of the selection targets to form breeding features in the pig industry. In this study, a customized Affymetrix Axiom Pig1.4M array plate was used to conduct genome-wide association studies (GWAS) for two exterior traits-spotted coat color (SC) and facial type (FT)-in Chinese Dongxiang spotted pigs. Two and 12 single nucleotide polymorphisms (SNPs) were identified to be associated with SC and FT at the 5% genome-wide s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…The most notable observation is the locus around 30.6 Mb on chromosome 7, which shows significant effects on multiple growth and carcass traits. It is needed to mention that the region on chromosome 7 was also identified in other local Chinese pig populations that have completely different genetic background with Bamaxiang pigs, these included Duroc × Erhualian F 2 resource population and Erhualian (He et al, ) and Dongxiang spotted pigs (Wang et al, ). However, the region was not identified for respective traits in pig breeds of mainly European origin like Large White and Landrace and Duroc, Cerdo Iberico, Large Black, Hampshire, Pietrain, and Schwabisch‐Hallisch (Rothammer et al, ), which suggested that the QTL segregate in Chinese indigenous pigs but not in the commercial pigs like Duroc, Large White and Landrace or above‐mentioned European indigenous pigs.…”
Section: Discussionmentioning
confidence: 99%
“…The most notable observation is the locus around 30.6 Mb on chromosome 7, which shows significant effects on multiple growth and carcass traits. It is needed to mention that the region on chromosome 7 was also identified in other local Chinese pig populations that have completely different genetic background with Bamaxiang pigs, these included Duroc × Erhualian F 2 resource population and Erhualian (He et al, ) and Dongxiang spotted pigs (Wang et al, ). However, the region was not identified for respective traits in pig breeds of mainly European origin like Large White and Landrace and Duroc, Cerdo Iberico, Large Black, Hampshire, Pietrain, and Schwabisch‐Hallisch (Rothammer et al, ), which suggested that the QTL segregate in Chinese indigenous pigs but not in the commercial pigs like Duroc, Large White and Landrace or above‐mentioned European indigenous pigs.…”
Section: Discussionmentioning
confidence: 99%
“…The phenotypic values were regressed on sex and batch, and the residuals were used as the new phenotypes. Then, a univariate linear mixed model regression was executed with phenotypic trait, genotype, and relatedness matrix files (Wang et al, 2018). The threshold of genomic significance was set by the Bonferroni method: 0.05/the number of tested SNPs (Yang et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…Samples were collected from ear tissues of 96 Dongxiang spotted pigs as described in our previous report [19]. Briefly, these 96 pigs were sampled from the nucleus population of Dongxiang spotted pigs in a national conservation farm in Dongxiang county, Jiangxi Province, China.…”
Section: Methodsmentioning
confidence: 99%
“…DNA quality was measured by spectrophotometry and agarose gel electrophoresis and was finally diluted to a concentration of 50 ng/μL. All 96 pigs were genotyped with a customized Affymetrix Axiom Pig1.4M array plate as previously described [19]. Briefly, a total of 1,362,630 SNPs were successfully genotyped for these 96 pigs.…”
Section: Methodsmentioning
confidence: 99%